Assessment of water quality of the Dhuppani waterfall and its advantages for the inhabitants of the Rangamati Hill Tracts, Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2026)
The present investigation aimed to evaluate seasonal fluctuations in water quality parameters of the Dhuppani waterfall, located in Rangamati, Bangladesh, with the goal of supporting local inhabitants and aquatic ecosystem conservation. Sampling was carried out over a one-year period from July 2022 to June 2023, encompassing the pre-monsoon, monsoon, and post-monsoon seasons. Water samples were collected from three designated stations and analyzed at the Water Quality Laboratory of the Department of Environmental Science and Resource Management, Mawlana Bhashani Science and Technology University, Tangail, Bangladesh. The parameters assessed included temperature, water transparency, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), pH, total alkalinity (TA), and total hardness (TH). The measured values ranged as follows: temperature (12.10 to 23.10°C), transparency (25 to 130 cm), EC (155 to 217 µS/cm), TDS (71 to 111 mg/L), DO (5.8 to 8.7 mg/L), BOD (0.49 to 1.05 mg/L), pH (6.10 to 8.20), TA (125 to 212 mg/L), and TH (72 to 185 mg/L). Analysis revealed that temperature, TDS, and BOD peaked during the pre-monsoon period and gradually declined through the monsoon and post-monsoon seasons. Conversely, EC and pH levels were found to be highest in the post-monsoon season, followed by the pre-monsoon and monsoon periods. Total alkalinity was at its maximum during the monsoon season, decreasing progressively in the post-monsoon and pre-monsoon phases. In contrast, total hardness showed a peak in the post-monsoon, followed by the monsoon, with the lowest values recorded during the pre-monsoon season. In the waterfalls, DO was higher in the monsoon season when compared to the post-monsoon and pre-monsoon seasons. Those physicochemical parameters furnish insights into water quality, ecosystem health, and potential water-related activities. The study provides baseline data on water quality from waterfalls in the Rangamati hill regions, which contributes to the long-term conservation of these aquatic ecosystems for human consumption and aquatic resource management.Int. J. Agril. Res. Innov. Tech. 15(2): 74-84, Dec 2025